2018
DOI: 10.1002/nau.23496
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic bladder in progressive supranuclear palsy: A comparison with Parkinson's disease and multiple system atrophy

Abstract: Urinary dysfunctions in PSP patients were as extensive as those with MSA, and were more severe than those with IPD, especially in the voiding phase. This may reflect the extensive degenerative process of neural structure in PSP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…Although all MSA patients reported urological symptoms, 8.2% had a normal urodynamic profile. Our data are comparable with those from other MSA studies, that reported percentages with a wide range of urodynamic pattern (detrusor overactivity 34–90%, 8 , 9 , 10 , 11 , 12 , 14 , 20 , 33 , 35 , 36 , 39 , 40 , 41 detrusor sphincter dyssynergia 16–56%, 8 , 10 , 14 , 20 , 35 , 36 , 41 detrusor underactivity 24–88% 8 , 10 , 11 , 12 , 20 , 34 , 36 , 40 ) likely based on different methodical issues. The urodynamic profile between MSA subtypes was basically equivalent with exception of one interesting finding reported in the following.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although all MSA patients reported urological symptoms, 8.2% had a normal urodynamic profile. Our data are comparable with those from other MSA studies, that reported percentages with a wide range of urodynamic pattern (detrusor overactivity 34–90%, 8 , 9 , 10 , 11 , 12 , 14 , 20 , 33 , 35 , 36 , 39 , 40 , 41 detrusor sphincter dyssynergia 16–56%, 8 , 10 , 14 , 20 , 35 , 36 , 41 detrusor underactivity 24–88% 8 , 10 , 11 , 12 , 20 , 34 , 36 , 40 ) likely based on different methodical issues. The urodynamic profile between MSA subtypes was basically equivalent with exception of one interesting finding reported in the following.…”
Section: Discussionsupporting
confidence: 91%
“…The presence of incomplete bladder emptying is an important clinical bedside marker, which can be measured without urodynamic examination and which in previous reports has been defined as a useful discriminator to distinguish MSA from PD. 8,9,20,[33][34][35][36][37][38] In 71.4% of the patients in the present cohort, postvoid residual volume was over 100 ml. Nonetheless, urodynamic evaluation might allow further important insights, which are discussed in detail in the following.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebral SVD is associated with urinary problems 19 and also with abnormalities on neurological examination, such as slowness of finger tapping. 20 Despite the possibility that these features might direct the attention of the treating physician towards the presence of a vascular contribution, other degenerative pathologies may present with similar findings 21,22 . It might be reasonable however to search for all these aspects in each patient arriving at a memory clinic.…”
Section: Clinical Expression Of Cerebrovascular Contribution In CImentioning
confidence: 99%
“… 109 110 111 Additionally, about two-thirds of patients with PD who exhibit urinary symptoms have urodynamically defined impaired detrusor contractility, resulting in voiding phase symptoms such as weak stream, hesitancy, and feelings of incomplete voiding. 112 Symptoms of sexual dysfunction including decrease in libido, erectile dysfunction in males, and decrease in lubrication in females are also frequent NMS, occurring in one-half to two-thirds of patients with PD. 111 113 114 115 116 Hypothalamic dysfunction due to altered dopamine-oxytocin circuit is thought to be responsible for the sexual dysfunction in PD because oxytocinergic neurons in the hypothalamus inhibit prolactinergic neurons that have an inhibitory effect on sexual function.…”
Section: Genitourinary Disordersmentioning
confidence: 99%